Economy, Poverty and Ethics - Estrella Egas, Manuel (2010)
The need for an ethical economy in nations is undeniable. Social awareness applied to economic policies can prevent polarization between dispossessed majorities and minorities with power and wealth, shortening the inequality gap between social groups. It is also clear that the production and extraction of resources require practices that work from a logic of rational use of non-renewable resources, since it is only under the guidance of ethical principles that progress can be made towards the construction of just States.